2017
DOI: 10.1063/1.4986390
|View full text |Cite
|
Sign up to set email alerts
|

Influence of residual charge on repetitively nanosecond pulsed dielectric barrier discharges in atmospheric air

Abstract: The plane-to-plane dielectric barrier discharge within 5 mm air gap driven by repetitive nanosecond pulses is studied. A water resistance (WR) is connected in parallel with the discharge circuit. For the discharge without the WR, two reverse discharges occur in the falling front of the voltage pulse, and besides, the primary discharge occurs in the rising front. For the discharge with the WR, only the primary discharge takes place, and the voltage waveform is changed into the unipolar positive voltage pulse wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Furthermore, while the voltage increases quickly, it decreases slowly. This indicates that secondary discharge does not occur, which is a current in the opposite direction commonly generated by residual charge in NPDBD [9,32]. I t was found to be slightly less than 2 A for both positive and negative discharges when measured through the probe resistor.…”
Section: Discharge Characteristicsmentioning
confidence: 86%
See 4 more Smart Citations
“…Furthermore, while the voltage increases quickly, it decreases slowly. This indicates that secondary discharge does not occur, which is a current in the opposite direction commonly generated by residual charge in NPDBD [9,32]. I t was found to be slightly less than 2 A for both positive and negative discharges when measured through the probe resistor.…”
Section: Discharge Characteristicsmentioning
confidence: 86%
“…Second, as previously stated, the residual charge accumulated on the dielectric within the discharge space causes specific areas to be discharged more strongly, increasing the likelihood of filamentary discharge [11]. A previous study in air at atmospheric pressure found that the discharge, which was uniform at 100 Hz, became nonuniform as the frequency increased to 1.2 kHz [9]. However, another study in low-pressure air at a low vacuum level yielded a nonuniform discharge when the frequency was reduced from 5 to 1 kHz.…”
Section: Discharge Characteristicsmentioning
confidence: 87%
See 3 more Smart Citations